Biodegradability Study by FTIR and DSC of Polymers Films Based on Polypropylene and Cassava Starch - Linares, Arturo Bismarck; Jiménez, Juan Carlos; López, Pedro; de Gáscue, Blanca Rojas (Orbital: The Electronic Journal of Chemistry, 2019)
The polypropylene resistance to biological attacks is related to the lack of functional groups recognizable by microbial enzymatic systems. The incorporation of compatibilizing agents in polypropylene (PP)/starch (S) blends favors the interactions of their components and can potentially induce the material degradation. In order to study the degradation of PP/S blends, films were prepared with a compatibilizing agent (AC), constituted by polypropylene grafted with acrylamide (PP-g-AAm). The films were placed in an Erlenmeyer flask containing 100 ml of a basal mineral medium with microorganisms inoculated in a cellulose filter, taken from an effluent. The FTIR analyzes of the films with the AC agent showed significant differences in the absorption bands, with respect to the control film. The asymmetric stretch signal of the grafted acrylamide that appeared at 3292 cm-1 increased in intensity only in the inoculated blends. In addition, hydrolysis was evidenced by the stretching signal of the OH bond. Abrupt changes were observed in the carbonyl region (1700-1600 cm-1) with the appearance of new bands, which shows the rupture of polymer chains. In the blends DSC analysis, a slight nucleation effect is observed in addition to a considerable increase in the degree of crystallinity, so it is suggested that the degradation could be occurring in the amorphous regions. DOI: http://dx.doi.org/10.17807/orbital.v11i2.1360